Management Of Thrips And Pod Borers Using Chemicals, Botanicals And Biopesticides In Mungbean - Islam, KN; Khan, MMH; Latif, MA; Uddin, MM; Islam, MM (SAARC Journal of Agriculture, 2020)
The experiment was conducted to find out effective control measure against thrips and pod borers of mungbean by various means, including chemicals, botanicals and biopesticide. The mungbean variety, BARI Mung-6 was grown in the field and six treatments viz., T1 [Azadirachtin (Bioneem plus 1EC)], T2 [Bacillus thuringiensis (Bt. powder)], T3 [Spinosad (Tracer 45SC)], T4 [Chlorpyrifos + Cypermethrin (Nitro 505EC)], T5 [Thiamethoxam + Chlorantraniliprole (Voliam flexi 300SC)] and T0 [Untreated control (water spray)] were set in randomized complete block design (RCBD) with three replications. The insecticidal treatment options showed significantly different performance against thrips (Megalurothrips distalis), gram pod borer (Helicoverpa armigera) and legume pod borer (Maruca vitrata) on mungbean. The lowest population of thrips, gram pod borer and legume pod borer was found in Voliam flexi 300SC treated plot which showed maximum percent reduction of these pests. The lowest percent pod infestation by pod borers observed by the same treatment. Bioneem plus showed the intermediate results considering all the parameters. The maximum yield (1254.50 kg ha-1) and the highest marginal benefit cost ratio (MBCR) (6.68) were obtained from Voliam flexi 300SC. Considering effectiveness and marginal benefit cost ratio, Voliam flexi 300SC was more effective among treatments for controlling thrips and pod borers of mungbean followed by Nitro 505EC. SAARC J. Agri., 17(2): 79-91 (2019)